ANALYSIS OF ACCOUNTING INFORMATION SYSTEMS AND CHANGE MANAGEMENT IN BUSINESS ACTIVITIES IN THE DIGITALIZATION ERA - Syarifuddin; Arifuddin; Qathrunnnada Atikah Hamka (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
Digital transformation has brought significant changes to accounting information systems (SIAs), making them not only a transaction recording tool, but also a strategic system to support decision-making. This research discusses the impact of digitalization on SIA, change management strategies in its implementation, and the importance of synergy between technology and management. The research uses a qualitative method with a literature study approach from various journals and books. The results of the discussion show that digitalization improves efficiency, accuracy, transparency, and internal control. However, the success of transformation relies heavily on human resource readiness, leadership support, and structured change management. The synergy between technology and management is the key to creating an adaptive, efficient, and sustainable accounting information system in the digital era.